Writing the love of boys : origins of Bishōnen culture in modernist Japanese literature - Angles, Jeffrey, 1971- (University of Minnesota Press, 2011)
Despite its centuries-long tradition of literary and artistic depictions of love between men, around the fin de siFcle Japanese culture began to portray same-sex desire as immoral. Writing the Love of Boys looks at the response to this mindset during the critical era of cultural ferment between the two world wars as a number of Japanese writers challenged the idea of love and desire between men as pathological. Jeffrey Angles focuses on key writers, examining how they experimented with new language, genres, and ideas to find fresh ways to represent love and desire between men. He traces the pe.